Principal’s Leadership Management for Coaching Teacher - Mujiati, Sri; Arafat, Yasir; Destiniar, Destiniar (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to identify and describe principal leadership management in teacher development at Air Salek State Elementary School 14. The method used is a qualitative method. Data collection techniques using observation, interviews and documentation. The results of this study indicate that teacher development is one of the principal’s duties. At SD Negeri 14 Air Salek, a five-year medium-term strategic plan has been prepared, namely 2018/2022 as well as an annual operational plan. This proves that the planning of teacher development at SD Negeri 14 Air Salek is well planned. The guidance of teachers at SD Negeri 14 Air Salek is also inseparable from the difficulties in achieving optimal coaching results. The obstacles faced include improving communication techniques. Thus, situations like these always impede learning and prevent teachers from reaching their potential. The solution to the problem is to take steps to train every teacher to communicate politely and effectively.